A dignitary in the land? literary representations of the american rabbi - Zierler, Wendy (2006)
The Haskalah of the late eighteenth century, it is often observed, dealt a major blow to many traditional Ashkenazic institutions, including the rabbinate. Formerly extolled by their communities in nearly God-like superlatives—such as “Chief shepherd, a dignitary in the land … Prince among princes in Torah and wisdom”—rabbis became the object of trenchant criticism during this period. The maskilim, formerly denizens of the yeshivot, cast special aspersion on rabbis and their assertion of the authority of Jewish law, charging that the rabbinic insistence on stringencies and legal minutiae was the source of all that was wrong with Diaspora Jewish life. Much of the critique of the rabbinate targeted the culture of yeshiva learning that supported it; the maskilim promoted the study of philosophy, science, Hebrew literature, and the scientific study of Judaism. Often, this literary and philosophical assault on the authority, role, and Talmud-centeredness of the rabbinate took the form of a critique of arranged marriages and the unequal status of women in Jewish law.
Keywords: Rabbis; Novels; Judaism; Jewish peoples; Jewish literature; Mothers; Jewish Identity; Torah; Jewish Law